Pore size and pore shape – but not mesh density – alter the mechanical strength of tissue ingrowth and host tissue response to synthetic mesh materials in a porcine model of ventral hernia repair. (February 2015) - Lake, Spencer P.; Ray, Shuddhadeb; Zihni, Ahmed M.; Thompson, Dominic M.; Gluckstein, Jeffrey; Deeken, Corey R.
Abstract: Background: Over 100 types of soft tissue repair materials are commercially available for hernia repair applications. These materials vary in characteristics such as mesh density, pore size, and pore shape. It is difficult to determine the impact of a single variable of interest due to other compounding variables in a particular design. Thus, the current study utilized prototype meshes designed to evaluate each of these mesh parameters individually. Methods: Five prototype meshes composed of planar, monofilament polyethylene terephthalate (PET) were evaluated in this study. The meshes were designed to focus on three key parameters, namely mesh density, pore size, and pore shape. The prototype meshes were implanted in the preperitoneal, retrorectus space in a porcine model of ventral incisional hernia repair, and tissue ingrowth characteristics were evaluated after 90 days. Mesh-tissue composite specimens were obtained from each repair site and evaluated via T-peel mechanical testing. Force–displacement data for each T-peel test were analyzed and five characteristics of tissue ingrowth reported: peak force ( f p ), critical force ( f c ), fracture energy ( Γ c ), work ( W ), and work density ( W den ). Hematoxylin and eosin (H&E) stained sections of explanted mesh-tissue composites were also assessed for characteristics of tissue response including cellular infiltration, cell types, inflammatory response, extracellular matrix deposition, neovascularization, and fibrosis, with a composite score assigned to represent overall tissue response. Results: The medium-weight, very large pore, hexagonal (MWVLH) mesh performed significantly better than the light-weight, medium pore, diamond (LWMD) mesh for all parameters evaluated ( f p, f c, Γ c, W, W den ) and trended toward better results than the medium-weight, medium pore, diamond (MWMD) mesh for the majority of the parameters evaluated. When the data for the five meshes was grouped to evaluate mesh density, pore size, and pore shape, differences were more pronounced. No significant differences were observed with respect to mesh density, however significant improvement in mechanical strength of tissue ingrowth occurred as pore size increased from medium to very large. In addition, the hexagonal pores resulted in the strongest tissue ingrowth, followed by the square pores, and finally the diamond pores. Scores for several histological parameters were significantly different for these prototype meshes. For example, the MWVLH mesh showed significantly greater tissue ingrowth by neovascularization histological score than MWMD and MWVLS meshes ( p <0.05) and significantly less fibrosis than LWMD and MWVLS meshes ( p <0.05). Conclusion: Pore shape and pore size significantly altered the mechanical strength of tissue ingrowth and host-site integration in a porcine model of ventral hernia repair, while mesh density had no effect. Graphical abstract: Highlights: Five prototype synthetic meshes were evaluated in a porcine hernia repair model. Meshes were designed with variable pore size/shape and mesh density. Mechanical strength of tissue ingrowth after 90 days assessed via T-peel testing. Pore size and pore shape affected mechanical strength of tissue ingrowth. Varied mesh density did not correspond with differences in integration.